Molecular biology of cantharidin in cancer cells - Rauh, Rolf (BioMed Central, 2007)
Herbal medicine is one of the forms of traditional medical practice. Traditional Chinese medicine (TCM) and traditional Vietnamese medicine (TVM) are well-known for their long-standing tradition of herbal medicine.